2010
DOI: 10.1111/j.1752-1688.2010.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Sediment Yield From Anjeni‐Gauged Watershed, Ethiopia Using SWAT Model1

Abstract: Setegn, Shimelis G., Bijan Dargahi, Ragahavan Srinivasan, and Assefa M. Melesse, 2010. Modeling of Sediment Yield From Anjeni‐Gauged Watershed, Ethiopia Using SWAT Model. Journal of the American Water Resources Association (JAWRA) 46(3):514‐526. DOI: 10.1111/j.1752‐1688.2010.00431.x Abstract:  The Soil and Water Assessment Tool (SWAT) was tested for prediction of sediment yield in Anjeni‐gauged watershed, Ethiopia. Soil erosion and land degradation is a major problem on the Ethiopian highlands. The objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 27 publications
5
103
0
1
Order By: Relevance
“…This result agrees with the findings of previous studies in northwest Ethiopian highlands. For example, ~25 t ha -1 y -1 (Setegn et al, 2010;Yeshaneh et al, 2014) and 8.6-55 t ha -1 y -1 (Mekonnen et al, 2015b). The result was also within the range of 3-49 t ha -1 y -1 found by Tamene et al (2006a) ) is the contribution of Minizr catchment.…”
Section: Sediment Transfer Pathwayssupporting
confidence: 56%
See 2 more Smart Citations
“…This result agrees with the findings of previous studies in northwest Ethiopian highlands. For example, ~25 t ha -1 y -1 (Setegn et al, 2010;Yeshaneh et al, 2014) and 8.6-55 t ha -1 y -1 (Mekonnen et al, 2015b). The result was also within the range of 3-49 t ha -1 y -1 found by Tamene et al (2006a) ) is the contribution of Minizr catchment.…”
Section: Sediment Transfer Pathwayssupporting
confidence: 56%
“…For example, in northwest Ethiopia, average annual sediment yield of 24.6 t ha -1 at Anjeni catchment (Setegn et al, 2010) and 13.6 t ha -1 at Angereb catchment (Amare, 2005) were reported. In the northern part of Ethiopia, the annual sediment yield of 10 catchments was estimated at 4-18 t ha -1 (Haregeweyn et al, 2008) and 3.4-49 t ha -1 (Tamene et al, 2006a) for another 11 catchments in the same region.…”
Section: Sediment Trapped By Sediment Storage Dams and Catchment Sedimentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the modeled sediment yield results for Minchet catchment to WLRC compiled sediment yield results and to other studies (Bosshardt, 1997;Setegn et al, 2010;Guzman et al, 2013;Lemann et al, 2016), which show reported mean annual sediment yields from 19.3 ha −1 y −1 to 29.5 ha −1 y −1 and resulting in an overall mean annual sediment yield of 26.12 ha −1 y −1 for the period of 1984 to 1993. The long term mean annual measured sediment yield from the WLRC grab samples for our study from 1984 to 2014 are 20.65 ha −1 y −1 while the SWAT modeled annual mean was 18.8 ha −1 y −1 (-8.95%).…”
Section: Catchment Water Balance and General Resultsmentioning
confidence: 99%
“…There have been numerous studies conducted in the Ethiopian highlands on modelling discharge and soil erosion with SWAT (Ndomba et al, 2008;Mekonnen et al, 2009;Setegn et al, 2010;Easton et al, 2010;Betrie et al, 2011;Notter et al, 2012;Yesuf et al, 2016;Lemann et al, 2016) to cite an incomplete list only. All of them focused on modeleling with limited measured data and none did attempt the model parameter transfer for lack of appropriate opportunities.…”
Section: Introductionmentioning
confidence: 99%